Genetics and reproduction - Goldberg, Daniella; Classroom Video (New South Wales : Classroom Video, 2001)
This program explores the revolution in genetic medicine and highlights the social and ethical implications of the emerging reproductive technolgies. The program looks at genetic testing as a means of preventing genetic disease and finding a genetically compatable mate. DNA testing is explained
Executive producer, John Davis ; editor, Dominique Fusy ; writer, Daniella Goldberg
VCD format
Keywords: Genetics; Biology